2016
DOI: 10.1007/s40261-015-0363-x
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Efficacy of Transcatheter Arterial Chemoembolization Followed by Sorafenib for Intermediate/Advanced Hepatocellular Carcinoma in Patients in Japan: A Retrospective Analysis

Abstract: Abstract, Results, line 2 which previously read: Although median tumor size was similar between groups, the mean tumor number was significantly higher in the S-TACE versus TACE-alone group (16 vs. 8, P = 0.04).Should read: Although median tumor size was similar between groups, the median tumor number was significantly higher in the S-TACE versus TACE-alone group (7 vs. 4, P \ 0.01).Page 751, Abstract, Results, line 9 which previously read:Median PFS (189 vs. 106 days, P = 0.02) and median overall survival time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…In addition, further analysis showed that tumor size ≥7 cm was also associated with poorer OS and PFS. These findings are in agreement with previous investigations that have identified Child-Pugh class, vascular invasion, tumor size, as well as BCLC stage, Eastern Cooperative Oncology Group (ECOG) performance status and alanine transaminase, as independent predictors of prognosis [ 47 49 ]. Although the tumor number and tumor size are both recognized as being associated with prognosis [ 50 ], a recent study has suggested that total tumor volume may be a better predictor of outcomes [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, further analysis showed that tumor size ≥7 cm was also associated with poorer OS and PFS. These findings are in agreement with previous investigations that have identified Child-Pugh class, vascular invasion, tumor size, as well as BCLC stage, Eastern Cooperative Oncology Group (ECOG) performance status and alanine transaminase, as independent predictors of prognosis [ 47 49 ]. Although the tumor number and tumor size are both recognized as being associated with prognosis [ 50 ], a recent study has suggested that total tumor volume may be a better predictor of outcomes [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported that the therapeutic strategy of early switching to sorafenib with TACE as a maintenance therapy prolonged progression-free survival (PFS) compared with repeated conventional TACE monotherapy in HCC patients unresponsive to TACE [ 23 , 24 ]. In the present study, we employed an index obtained by dividing the total number of radiofrequency ablation (RFA), TACE, and transcatheter arterial infusion (TAI) procedures by the years of survival to evaluate the efficacy of repeated TACE monotherapy and early switching from TACE to sorafenib therapy on OS.…”
Section: Introductionmentioning
confidence: 99%
“…Ohki T et al found that median overall survival time (861 vs. 467 days, P = 0.01) from the time of nonresponsiveness to TACE were signi cantly longer with TACE followed by sorafenib within 14 days than TACE alone. (27) Kaplan-Meier survival curve analysis was done using log-rank test for possible risk factors for survival period and hazards ratios with 95% con dence interval and it was observed that of all risk factors highest hazard was found with a multifocal lesion (2.0577) and results were signi cantly higher than unifocal lesion (95 % con dence interval: 0.9225 to 4.5900, p 0.0451) with median survival period of 7 vs 9.5 months. Similarly, it was observed in the present study that age < 59 years, KPS ≤ 60, male gender, alcoholic, HbsAg reactive, presence of portal vein thrombosis had 1.0933, 1.8792, 1.8267, 1.2647, 0.8182, and 1.2749 times more hazard as compared to age ≥ 59 years, KPS > 60, female gender, non-alcoholic, HbsAg non-reactive and absence of portal vein thrombosis with a median survival period of 7 vs 7.5 months, 6.5 vs 8 months, 7 vs 9.5 months, 7 vs 8 months, 7 vs 7.5 months, 6.5 vs 8 months respectively.…”
Section: Association Between Possible Risk Factors and Survivalmentioning
confidence: 99%